Productivity and profitability of sesame (Sesamum indicum)- chickpea (Cicer arietinum) organic cropping system as influenced by nutrition and planting geometry - KUMAR, NARINDER; SINDHU, V K; SIDHU, A S; AULAKH, C S (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2021–22 and 2022–23 at the research farm of Punjab Agricultural University, Ludhiana, Punjab to optimize organic nutrition and planting geometry for improved productivity and profitability of sesame (Sesamum indicum L.)-chickpea (Cicer arietinum L.) organic cropping system. The experiment was conducted in a split-plot design (SPD) with three organic nutrition management practices in main plots, viz. Application of farmyard manure (FYM) to supply recommended doses of nitrogen (RDN) i.e. 52.5 kg/ha for sesame and 15 kg/ha for chickpea; Application of FYM to supply RDN + natural farming concoctions (NFCs) i.e. beejamrit, ghanjeevamrit and jeevamrit; and Control i.e. without application of FYM and NFCs. In sub-plots, four planting geometries were evaluated for sesame (30 cm × 15 cm, 45 cm × 10 cm, 60 cm × 10 cm, and paired rows) and chickpea (30 cm × 10 cm, 45 cm × 7 cm, 60 cm × 7 cm, and bed planting). Application of FYM significantly improved growth, yield attributes and seed yield of sesame and chickpea compared to the control, whereas the addition of NFCs along with FYM did not further enhance these parameters significantly during both the years. Paired row sowing followed by (fb) bed formation led to notably higher seed yield in sesame, while chickpea sown at 30 cm × 10 cm spacing achieved the highest seed yield, statistically equivalent to sowing at 45 cm × 7 cm and bed planting. The most productive system, recorded a sesame equivalent yield of 18.1 q/ha, net returns of ₹1,06,224/ha, and a benefit cost (B:C) ratio of 1.51, achieved through paired row sowing of sesame and bed planting of chickpea. Conclusively, the optimized organic nutrition and planting geometry significantly enhanced the productivity and profitability of the sesame-chickpea cropping system, with paired row sowing and bed planting emerging as the most effective strategies.